2004
DOI: 10.1128/aem.70.6.3582-3587.2004
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Chain Fatty Acids Decrease Colonization and Invasion through hilA Suppression Shortly after Infection of Chickens with Salmonella enterica Serovar Enteritidis

Abstract: The most common source of Salmonella infections in humans is food of poultry origin. Salmonella enterica serovar Enteritidis has a particular affinity for the contamination of the egg supply. In this study, the medium-chain fatty acids (MCFA), caproic, caprylic, and capric acid, were evaluated for the control of Salmonella serovar Enteritidis in chickens. All MCFA were growth inhibiting at low concentrations in vitro, with caproic acid being the most potent. Contact of Salmonella serovar Enteritidis with low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(142 citation statements)
references
References 23 publications
4
133
3
2
Order By: Relevance
“…Salmonella Typhimurium strains carrying the plasmid containing either the hilA-luxCDABE or the ssrA-luxCDABE transcriptional fusions were used in the virulence gene expression experiments [5]. For fluorescence microscopy, the pFPV25.1 plasmid expressing green fluorescent protein under the constitutive promoter of rpsM was used [6,35,36].…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Salmonella Typhimurium strains carrying the plasmid containing either the hilA-luxCDABE or the ssrA-luxCDABE transcriptional fusions were used in the virulence gene expression experiments [5]. For fluorescence microscopy, the pFPV25.1 plasmid expressing green fluorescent protein under the constitutive promoter of rpsM was used [6,35,36].…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…However, in other research where chickens were delayed fed for 1 or 2 days, the mortality risk was not affected (Corless and Sell, 1999). In chickens that were infected with the malabsorption syndrome, inclusion of MCFA resulted in a lower mortality risk (Gutierrez Del Alamo et al, 2007) of which the effect was contributed to the antimicrobial properties of MCFA (Van Immerseel et al, 2004). Inclusion of MCFA in a pre-starter diet can be hypothesized to have similar antimicrobial properties, possibly preventing the colonization of pathogenic microflora associated with increased mortality risk.…”
mentioning
confidence: 99%
“…Studies on the biological effects of coconut oil have proven that it ameliorates oxidative stress by boosting the antioxidant defense system, mopping up free radicals and reducing lipid peroxidation [4,5]. It has also been reported to suppress microbial and viral activities [6], promote weight loss and enhance thyroid function [7]. Other researches have also reported that coconut oil possesses anti-inflammatory and anti-ulcerogenic effect [8], while also having the ability to increase the level of high density lipoprotein (HDL) cholesterol and to reduce the level of low density lipoprotein (LDL) in serum and tissues [4].…”
Section: Introductionmentioning
confidence: 99%